STRATEGIC MANAGEMENT ANALYSIS ON THE IMPLEMENTATION OF SCHOOL CULTURE BASED ON THE 2020 ACCREDITATION INSTRUMENT IN MIN BANDUNG - Akhmaliah Siti Nailan; Mulyawan Safwandy Nugraha (PIONIR: JURNAL PENDIDIKAN, 2024)
This study is inspired by the potency of positive school culture in enhancing education quality, especially within the madrasah environment. A strong school culture has been considered crucial, but efforts toward strong strategic management to support the school culture still face many challenges. Among the most urgent issues are adjustments to the constantly evolving standards for accreditation, such as the 2020 Accreditation Certification Tool. The present study analyzes how strategic management influences the school culture to achieve standards in MIN Bandung. This case study, using a qualitative approach, has collected data through in-depth interviews, observation, and documentation, then analyzed using thematic techniques in identifying management patterns that support school culture. It is observed that MIN Bandung can instill into the culture the values of honesty, cooperation, and compassion, so that student motivation positively influences performance. On the contrary, what needs to be faced in the current era is the sustainability of value implementation and resource limitation. The conclusion suggests that the strategy should become more adaptive and holistic to be compatible with the 2020 accreditation standards.Keywords: Strategic management, school culture, accreditation.